Avaliação da aprendizagem à luz da pedagogia histórico-crítica : contribuições para a formação de professores - Castro, Tainara Pereira (2017)
This dissertation has as object of study the evaluation learning in the childhood education and, in this way, we made a survey of the literature that evidences the absence of productions on this subject, mainly, based on the referential of historical-critical pedagogy, what that has caused worries that mobilized us to the development this research, because it is essential to reveal the contributions of this pedagogical theory to the organization of evaluation processes. Taking as base of the analysis the referential of historical-critical pedagogy, we elected the following research questions: 1) What is the theoretical predominance in studies of the area of evaluation of school learning and what are the epistemological foundations underlying the productions about the learning evaluation? 2) What epistemological foundations have subsidized the National Curriculum Guidelines for Early Childhood Education, as far as learning assessment is concerned? 3) What contradictions are evidenced in the discussions about evaluation in early childhood education? Considering the theme of this research, we established as general objective to analyze, based on the presuppositions of historical-critical pedagogy, the predominance of studies in the area of evaluation of school learning in childhood education, seeking their contradictions and possibilities. Thus, we define as specific objectives: to identify the conception of evaluation and the most predominant epistemological foundations in the academic productions found in the Brazilian Digital Library of Theses and Dissertations; to examine the epistemological foundations that have subsidized the National Curriculum Guidelines for Early Childhood Education on the evaluation of school learning; to clarify the contradictions present in the discussions about the evaluation learning in Early Childhood Education. What is the predominance in studies of the area of evaluation of school learning and what are the epistemological foundations adjacent to the productions about learning evaluation? What contradictions are evident in the discussions about evaluation in early childhood education? In the face of such contradictions, what are the contributions of historical-critical pedagogy to the understanding of learning assessment? This research is of a theoretical nature, bibliographical and documentary. The results point two contradictions surrounding the discussions on evaluation in early childhood education: we do not perceive, in the documents analyzed or in the most cited authors in the academic productions, a rupture with the ideology defended by the neoliberal logic, but rather an alignment to it, fact that goes against the real and necessary interests of the working class. In view of the hegemony of a discourse that is linked to the ideary of "learning to learn," another contradiction resulting from this alliance with the neoliberal project refers to the increasing emptying of school content, whether historical, artistic or philosophical. Our defense is that early childhood education needs to have teaching as the axis for its organization. In an attempt to signal some elements about the evaluation learning in the context of historical-critical pedagogy, we understand that it constitutes herself as a mediating activity within the educational practice, as it interposes between the activity of teaching and the learning activity. To understand evaluation as a mediating activity means to overcome the idea of mediation as a link or bridge and to understand it as a movement of activity that interpose herself over the poles of "activity of teaching" (teacher) and "learning activity" (student), capturing their relations and surpassing them, promoting the transformation of the whole set.